Academic Burnout, Self-Efficacy, and Emotional Stress Reaction of Learners: Conditional Process Analysis - Arhin, David; Adu-Mensah, Jephtar; Adom, Dickson; Annan-Brew, Ruth (International Journal of Membrane Science and Technology, 2023)
Academic burnout lessens learners' insights into their ability to study and their academic achievement, as well as has a detrimental effect on their physical and mental health, which may be tied to an emotional stress reaction. The current study aimed to assess academic burnout, self-efficacy, and emotional stress reaction of sandwich learners through conditional process analysis. For the study, a descriptive survey with a sample size of 385 students who represented a reachable population of 1, 925 respondents was used. Data was collected using a questionnaire with r = .776 through online Google format. Frequencies, percentages, the Pearson product-moment r, and a structural equational model were used to analyze the data. According to the study, there are three levels of self-efficacy for students. However, the study found that most learners have moderate self-efficacy. The study also revealed that there is no substantial relationship between learners’ self-efficacy and their emotional stress reactions. It was again found that self-efficacy significantly moderates the influence of academic burnout on emotional stress reactions. Finally, the study found that self-efficacy does not significantly mediate the influence of academic burnout on emotional stress reactions. After these predominant findings, it was concluded that the majority of learners tend to exhibit moderate self-efficacy. This implies that while they possess a certain degree of confidence in their abilities, there is room for improvement and growth in terms of their self-belief. It is advised that educational institutions and teachers concentrate on interventions and tactics to improve students' self-efficacy in light of these findings.